Popular English Songs in Tiktok to Teach English Vocabulary: A Mixed-Method Study - Romi, Stefanni Nanda (English Education Department STKIP Agama Hindu Singaraja, 2025)
Although TikTok has been widely utilized as an educational medium, there remains a lack of empirical research examining its specific impact on vocabulary acquisition. Therefore, this study examined the impact of using popular TikTok songs as a medium for teaching English vocabulary to students at Madrasah Tsanawiyah Negeri 2 Buleleng. With a mixed-methods approach, the research integrated a quasi-experimental design with qualitative observations to assess the effectiveness of TikTok-based vocabulary learning compared to conventional teaching methods. This study involved two groups: an experimental class, where students learned vocabulary through selected TikTok songs, and a control class, which followed a traditional textbook-based approach. Data were collected through pre-tests and post-tests to measure vocabulary acquisition, along with classroom observations to evaluate student engagement and participation. The findings revealed a significant improvement in vocabulary mastery among students in the experimental group, with their average score increasing from 63.52 in the pre-test to 83.22 in the post-test. Meanwhile, students in the control group showed only a slight improvement, from 64.00 in the pre-test to 67.76 in the post-test. The implications of the significant improvement in vocabulary mastery among students in the experimental group suggest that integrating popular TikTok songs into English vocabulary instruction can effectively enhance learning outcomes. This approach not only improves students' vocabulary acquisition more substantially than traditional methods but also indicates that engaging, culturally relevant digital media can serve as a powerful tool to boost motivation, participation, and confidence in language learning. This study highlights the potential of social media as an educational tool and encourages educators to explore creative, student-centered approaches to enhance language learning outcomes.